Relationship of Meteorological and Air Pollution Parameters with Pneumonia in Elderly Patients - Suleyman Serdar Tasci; Cemil Kavalci; Afsin Emre Kayipmaz (Emergency Medicine International)
Background and Purpose. In this study, we aimed to evaluate the relationship between pneumonia and meteorological parameters (temperature, humidity, precipitation, airborne particles, sulfur dioxide (SO2), carbon monoxide (CO), nitrogen dioxide (NO2), nitrite oxide (NO), and nitric oxide (NOX)) in patients with the diagnosis of pneumonia in the emergency department. Methods. Our study was performed retrospectively with patients over 65 years of age who were diagnosed with pneumonia. The meteorological variables in the days of diagnosing pneumonia were compared with the meteorological variables in the days without diagnosis of pneumonia. The sociodemographic characteristics, complete blood count of the patients, and meteorological parameters (temperature, humidity, precipitation, airborne particles, SO2, CO, NO2, NO, and NOX) were investigated. Results. When the temperature was high and low, the number of days consulted due to pneumonia was related to low air temperature (p<0.05). During the periods when PM 10, NO, NO2, NOX, and CO levels were high, the number of days referred for pneumonia was increased (p<0.05). Conclusion. As a result, climatic (temperature, humidity, pressure levels, rain, etc.) and environmental factors (airborne particles, CO, NO, and NOX) were found to be effective in the number of patients admitted to the hospital due to pneumonia.